Recurrent rectal cancer cured by transsacral prone longitudinal incision combined with bilateral gluteus maximus “kite” flap filling: a case report - Zhang, Lixia; Jiang, Xiaoling; Wu, Maoyuan; Zhang, Wenwen; Wang, Guanyan; Yang, Wei; Li, Tingchao; He, Lianli; Wang, Gangcheng (Frontiers in Oncology, 2025)
Locally recurrent rectal cancer (LRRC) refers to the lesions that appear in the pelvic cavity and perineum with the same pathological type as the primary tumor after radical operation of rectal cancer, excluding other distant metastases such as liver, lung, and bone. Radical surgical resection in such patients is a central element in improving quality of life andsurvival. In this paper, we report the case of a patient who was admitted to our hospital with a recurrence of ulcerated moderately differentiated carcinoma of the lower rectum with vaginal involvement after comprehensive treatment. After discussion by a multidisciplinary team, a transsacral prone longitudinal incision combined with bilateral gluteus maximus “kite” flap padding was used to remove the tumor tissue completely, and the postoperative area healed well, which improved the patient’s quality of life and increased her survival rate.